Business demography dynamics in Portugal: a non-parametric survival analysis - Nunes, Alcina (2014)
Over the last four or fi ve decades, advanced economies have been confronted to tremendous changes and challenges. Adopting a global or macro-view can help in identifying social and economic stylized facts. Audretsch and Thurik (2000, 2001) and Thurik (2011) distinguish two polar economies according to which economic stylized facts can be reinterpreted and reordered. The managerial model articulates economic growth around mass production, specialization, certainty, predictability and homogeneity, allowing the full play of economies of scale. The model of the entrepreneurial economy articulates economic growth around a variety of needs, novelty, turbulence, innovation and functioning in networks, allowing the full play of entrepreneurial fl exibility. By observing recent social and economic trends in advanced economies, including European economies, one may consider that a transition from a managerial to an entrepreneurial economy has been taking place since the late seventies/early eighties. The factors and mechanisms for the transition to take place are numerous. However, Stam (2008) identifi es three main sources that may be evoked to explain the emergence of new entrepreneurial opportunities.